1992
DOI: 10.1073/pnas.89.23.11282
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of trkB mRNA and trkB protein-like immunoreactivity in the injured rat and cat spinal cord.

Abstract: Expression of neurotrophins and neurotroph-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
1

Year Published

1994
1994
1999
1999

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 40 publications
2
74
1
Order By: Relevance
“…Conversely, the expression of TrkA in peripheral nerves and sensory corpuscles is conflicting, although we observed TrkA-like IR as a regular feature of perineurial and corpuscular perineurial-related cells as well as corpuscular Schwannrelated cells. Neither TrkA mRNA nor TrkA was detected in Schwann cells (Funakoshi et al, 1993;Yamamoto et al, 1993;Anton et al, 1994;Liu et al, 1995;Offenhausser et al, 1995), but it was localized in meningeal and nonnervous cells sheathing the ventral root of rat spinal nerves (Risling et al, 1994) and in leptomeningeal cells (Frisen et al, 1992) which share the origin with perineurial cells (Halata et al, 1990). On the other hand, observations in Merkel cells regarding p75 are in good agreement with previous reports (Ribeiro da Silva et al, 1991;Narisawa et al, 1992;Vega et al, 1992;English et al, 1994).…”
Section: Nerves and Sensory Corpusclessupporting
confidence: 82%
“…Conversely, the expression of TrkA in peripheral nerves and sensory corpuscles is conflicting, although we observed TrkA-like IR as a regular feature of perineurial and corpuscular perineurial-related cells as well as corpuscular Schwannrelated cells. Neither TrkA mRNA nor TrkA was detected in Schwann cells (Funakoshi et al, 1993;Yamamoto et al, 1993;Anton et al, 1994;Liu et al, 1995;Offenhausser et al, 1995), but it was localized in meningeal and nonnervous cells sheathing the ventral root of rat spinal nerves (Risling et al, 1994) and in leptomeningeal cells (Frisen et al, 1992) which share the origin with perineurial cells (Halata et al, 1990). On the other hand, observations in Merkel cells regarding p75 are in good agreement with previous reports (Ribeiro da Silva et al, 1991;Narisawa et al, 1992;Vega et al, 1992;English et al, 1994).…”
Section: Nerves and Sensory Corpusclessupporting
confidence: 82%
“…Thus, the injury-related effects on the survival of neurons in the retina may be due to the intraocular synthesis and release of molecules that are specific trophins for RGCs. By analogy with injury-induced responses in other parts of the CNS, RGC survival can also be influenced by changes in the expression of specific receptors (29) or by the synthesis and release of other trophic molecules known to be present in the eye such as acidic or basic fibroblast growth factors (30) and ciliary neurotrophic factor (31). Our finding that anterior ocular injections had a more prolonged survival effect than posterior injections suggests that the critical molecules may be released from endogenous sources in a protracted fashion.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, there is abundant evidence supporting the concept that neurotrophins and their receptors have a protective effect on many neuronal populations after injury (Sendtner et al, 1992;Yan et al, 1992Yan et al, , 1993Koliatsos et al, 1993;Arenas and Persson, 1994;Li et al, 1994). For instance, it has been shown that axotomy results in changes in the expression of neurotrophins and p75 and Trk receptors in neurons, glial cells, and target tissues (Heumann et al, 1987;Ernfors et al, 1989;Frisén et al, 1992Frisén et al, , 1993Meyer et al, 1992;Beck et al, 1993;Funakoshi et al, 1993;Koliatsos et al, 1993;Mearow et al, 1993;Merlio et al, 1993;Piehl et al, 1994;Kobayashi et al, 1996). Furthermore, exogenously administered neurotrophins can rescue neurons from injury-induced cell death in axotomy paradigms (Sendtner et al, 1992;Yan et al, 1992;Koliatsos et al, 1993Koliatsos et al, , 1994Yan et al, 1993;Arenas and Persson, 1994).…”
Section: Abstract: Trkb; Cns; Cell Death; Axotomy; Hippocampus; Motomentioning
confidence: 99%